Variables Affecting Shoot Growth and Plantlet Recovery in Tissue Cultures of Drug-Type Cannabis sativa L. - Holmes, Janesse E.; Lung, Samantha; Collyer, Danielle; Punja, Zamir K. (Frontiers in Plant Science, 2021)
Tissue culture approaches are widely used in crop plants for the purposes of micropropagation, regeneration of plants through organogenesis, obtaining pathogen-free plantlets from meristem culture, and developing genetically modified plants. In the present research, we evaluated the variables that can influence the success of shoot growth plantlet production from tissue cultures of Cannabis sativa L. (marijuana). Various sterilization methods were tested to ensure shoot development from nodal explants by limiting the frequency of contaminating endophytes, which otherwise caused death of explants. Seven commercially grown THC-containing cannabis strains showed significant differences in response to shoot growth from nodal explants and from meristems on Murashige and Skoog (MS) medium containing thidiazuron (1µM) and naphthaleneacetic acid (0.5 µM) plus 1% activated charcoal. The effect of DWK or MS salts in media on shoot length and leaf numbers from nodal explants was compared and showed strain dependency with regards to the growth response. To obtain rooted plantlets, shoots from nodal and meristem explants of strain Moby Dick were evaluated for rooting following addition of sodium metasilicate, silver nitrate, IBA, kinetin, or 2,4-D. Sodium metasilicate improved the visual appearance of the foliage, and improved the rate of rooting. Silver nitrate also promoted rooting. Following acclimatization, plantlet recovery using hydroponic culture, peat plugs, and rockwool substrate was 57, 76 and 83%, respectively. The development of plantlets from meristems is described for the first time in C. sativa and has potential for obtaining pathogen-free plants. The response of leaf explants to callus formation in 11 strains on MS medium without activated charcoal was 35 to 100%, depending on the strain; organogenesis was not observed. The success in recovery of plantlets from nodal and meristematic explants is influenced by the cannabis strain and the degree of endophytic contamination of the explants, as well as frequency of rooting. The procedures described here have potential applications for research and commercial utility to obtain plantlets from tissue cultures of C. sativa.